2018
DOI: 10.1021/acsnano.7b06417
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Synthesis of Molybdenum Carbide and Formation of a Mo2C/MoS2 Hybrid Structure via Chemical Conversion of Molybdenum Disulfide

Abstract: The epitaxial synthesis of molybdenum carbide (MoC, a 2D MXene material) via chemical conversion of molybdenum disulfide (MoS) with thermal annealing under CH and H is reported. The experimental results show that adjusting the thermal annealing period provides a fully converted metallic MoC from MoS and an atomically sharp metallic/semiconducting hybrid structure via partial conversion of the semiconducting 2D material. MoC/MoS hybrid junctions display a low contact resistance (1.2 kΩ·μm) and low Schottky barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 60 publications
5
114
0
Order By: Relevance
“…The epitaxial growth of TMCs on ever‐formed sulfide surface is a conventional strategy to design carbide‐sulfide heterostructures. Jeon et al demonstrated the epitaxial synthesis of 2D metallic Mo 2 C layers on MoS 2 crystals via carburizing exfoliated MoS 2 flakes under CH 4 and H 2 , with Cu foil as a catalyst ( Figure a) . The converted Mo 2 C area was experimentally shown to depend on the thermal annealing period (Figure b,c).…”
Section: Heterostructures Of Tmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epitaxial growth of TMCs on ever‐formed sulfide surface is a conventional strategy to design carbide‐sulfide heterostructures. Jeon et al demonstrated the epitaxial synthesis of 2D metallic Mo 2 C layers on MoS 2 crystals via carburizing exfoliated MoS 2 flakes under CH 4 and H 2 , with Cu foil as a catalyst ( Figure a) . The converted Mo 2 C area was experimentally shown to depend on the thermal annealing period (Figure b,c).…”
Section: Heterostructures Of Tmcsmentioning
confidence: 99%
“…f,g) Low‐magnification STEM images of the Mo 2 C−MoS 2 junction (upper panel) and high‐magnification STEM images taken from the blue rectangle in the upper image (lower panel) and EELS element mapping image of the sulfur L‐edge (g) and carbon K‐edge (f), over the area indicated by the red rectangle in (f). Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Heterostructures Of Tmcsmentioning
confidence: 99%
“…Unlike precise element doping, the fabrication of hybrid structures of TMDs and co‐catalysts is more feasible. Systematic investigations suggested that the TMDs layer can be converted to other phases, i.e., the carbonization and nitridation of the MoS 2 to form MoC x and MoN x , [ 127–129 ] which have the outstanding catalytic performance on HER owing to the hybridization between the d‐orbitals of Mo and the s‐ and p‐orbitals of C/N, giving similar d‐band electronic structure with Pt. [ 130–132 ] The synergistic effect (e.g., the improved charge injection from the co‐catalyst) and the tuned Δ G H* at the interface of the hybrid structure offer additional opportunities in improving the HER performance.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
“…Such positive effect of the interface is also applicable in various reported hybrid structures such as the MoS 2 /Mo 2 C on N doped carbon nanotubes (CNTs), [ 133 ] the WS 2 /W 2 C on N‐ and S‐decorated carbon matrix, [ 134 ] the S‐decorated Mo 2 C, [ 135 ] and the N, S co‐doped Mo 2 C nanosheets. [ 136 ] According to the previous DFT calculations, the formation of the hybrid interface between multilayered TMDs (e.g., MoS 2 ) and carbon materials is exothermic and favorable, [ 129 ] giving the tuned Δ G H* to favor for the H adsorption/desorption, and the “ohmic contact” to low down the charge transfer resistance. This phenomenon explains well why the HER catalytic performance of some hybrid structures of TMDs and carbon materials, such as the MoSe 2 and CNTs, [ 137 ] the MoS 2 /MoSe 2 and graphene, [ 138,139 ] were significantly superior to their pure phases or mixtures.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
“…The prominent activity of hydrotreating catalysts depends on the potential of the active sites, and the structure and textural characteristics of the supports. [5][6][7] Generally, alumina is used as a support as it is economical and possesses unique physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%